Spatial Analysis of COVID-19 in Zacatecas, Mexico: Local spatial patterns and influential factors - Terán-Hernández, Mónica; Campos-Alanís, Juan; Rivas Santiago, Bruno; González Curiel, Irma Elizabeth (CIENCIA ergo-sum; Vol. 32 (2025): CIENCIA ergo-sum, 2024)
Spatial analysis-based planning (SABP) is vital for addressing priority issues. The study aimed to analyze local spatial patterns and factors influencing the distribution of COVID-19 in Zacatecas through GIS and geostatistical methods. The Bayesian rate was calculated and GWLR models adjusted. Local patterns were evident, showing a relationship between COVID-19 and comorbidities, marginalization index, and 911 calls for gender violence. Three significant hot spots were identified in areas with greater inequalities. Isn’t just about identifying a hot spot, is analyzing that the causal relationship between comorbidities and COVID-19 is particularly pronounced, these are the places where we can think in terms of SABP to support public health policy to modify pre-existing conditions not just about this current pandemic.